Recovery of Ductility in Ultrafine-Grained Low Carbon Steel Processed by Electropulsing - Bhuyan D.; Pandey R.K.; Ojha S.N.; Sastry G.V.S.; Choudhary H.; Sharma A.; Manna R. (My University, 2025)
Workpieces of a low carbon steel (LCS) are deformed by equal-channel angular pressing (ECAP) up to an equivalent strain of 6 in their as-received, coarse-grained condition. ECAP of LCS produces an ultrafine-grained (UFG) banded structure of 0.6 μm in width, with a high dislocation density and lattice strain. Though the refinement improves strength significantly, the material suffers from a detrimental low ductility. ECAPed samples are therefore electropulsed to recover the ductility to a large extent. A mechanism, by which a unique microstructure that fecilitates the regainment of ductility, is proposed in this study. Electropulsing (EP) creates additional low angle grain boundaries (LAGBs) by electromigration of dislocations within the grain and leads to the migration of high angle grain boundaries (HAGBs) under high electron wind force. Groups of subgrain boundaries move towards high angle grain boundaries and coalesce, producing a region of relatively lower defect density, i.e., the formation of recrystallized nuclei. On further pulsing, the HAGBs of the recrystallized nuclei continue to migrate and eventually impinge on each other. As a result, a bimodal grain size distribution consisting of micron-sized, near-equiaxed grains that are favorably interspersed with UFG grains occurs, and has a low defect density. The microstructure is clear of any residual strain. Upon electropulsing the strength of ECAPed LCS is marginally traded off for a larger gain in ductility. The micron-sized grains of the bimodal distribution are understood to accommodate larger deformations and enhance the ductility. © 2021, The Minerals, Metals & Materials Society and ASM International.